Microplastic Leaching in Local Candy, Pickles and Yogurt Packed in Plastic Containers - Kour, Jagjit; Bhatt, Pratima (Journal of Nepal Chemical Society, 2022)
Plastics degrade into nano plastic or microplastic. Microplastics (MPs) leaches from plastic packaging to food affect human health. In this study overall migration of different plastics packaging was determined by using IS 9845: 1998 method. Food simulant distilled water (Simulant A) for aqueous/non acidic foods (pH ≥ 5) without fat, 3% acetic acid (simulant B) for aqueous, acidic food (pH≤ 5) without fat at 40°C/10 days and n-heptane (simulant D) for edible fatty foods at 38°C/0.5 were used as per Bureau of Indian Standards IS - 9845-1998. Overall migration in local candy (Titaura) ranges from 4.51580 to 20.43310 mg/kg in food simulant 3% acetic acid (simulant B) and by using n-heptane (simulant D) it ranges from 12.2400 to 41.1066 mg/kg. Similarly in pickles migration of microplastics range from 51.16 to 58.56 mg/kg by using simulant B and in the case of simulant D, it ranges from 7.2266 to 58.6266 mg/kg. The overall migration of microplastics in Yogurt samples were found to be 3.0186 to 19.2093 mg/L using simulant B and in the case of simulant D, it ranges from 7.2266 to 58.6266 mg/L.